Wealth and Poverty in Jewish Tradition - Greenspoon, Leonard (Purdue University Press, 2015)
Economic inequity is an issue of worldwide concern in the twenty-first century. Although these issues have not troubled all people at all times, they are nonetheless not new. Thus, it is not surprising that Judaism has developed many perspectives, theoretical and practical, to explain and ameliorate the circumstances that produce serious economic disparity. This volume offers an accessible collection of articles that deal comprehensively with this phenomenon from a variety of approaches and perspectives. Within this framework, the fourteen authors who contributed to Wealth and Poverty in Jewish Tradition bring a formidable array of experience and insight to uncover interconnected threads of conversation and activities that characterize Jewish thought and action. Among the questions raised, for which there are frequently multiple responses: Is the giving of tzedakah (generally, although imprecisely, translated as "charity") a command or an impulse? Does the Jewish tradition give priority to the donor or to the recipient? To what degree is charity a communal responsibility? Is there something inherently ennobling or, conversely, debasing about being poor? How have basic concepts about wealth and poverty evolved from biblical through rabbinic and medieval sources until the modern period? What are some specific historical events that demonstrate either marked success or bitter failure? And finally, are there some relevant concepts and practices that are distinctively, if not uniquely, Jewish? It is a singular strength of this collection that appropriate attention is given, in a style that is both accessible and authoritative, to the vast and multiform conversations that are recorded in the Talmud and other foundational documents of rabbinic Judaism. Moreover, perceptive analysis is not limited to the past, but also helps us to comprehend circumstances among today's Jews. It is equally valuable that these authors are attuned to the differences between aspirations and the realities in which actual people have lived.